Talking to My Tatas: All You Need to Know from a Breast Cancer Researcher and Survivor - Brantley-Sieders, Dana (Rowman & Littlefield Publishers, 2022)
With humor and empathy, Dana Brantley-Sieders explores the science and realities of breast cancer for the love of your boobs and your life. Dana Brantley-Sieders spent twenty years working as a biomedical breast cancer researcher. Then, she was diagnosed with breast cancer. She thought she knew breast cancer before it whacked her upside her left boob and left her bleeding on the curb of uncertainty. Turns out, she had a lot to learn. This book shares Brantley-Sieders’ personal journey with breast cancer, from the laboratory bench to her own bedside, and provides accessible information about breast cancer biology for non-scientists. Talking to My Tatas: All You Need to Know from a Breast Cancer Researcher and Survivor, offers accurate, evidence-based science that is accessible to all readers, including the more than three hundred thousand individuals diagnosed with breast cancer every year, their caregivers, and their loved ones. Knowledge is power, and lack of it can lead to overtreatment, unnecessary pain and suffering, and even death. By demystifying the process from mammograms, biopsies, pathology, and diagnostics, to surgical options, tumor genomic testing, and new treatment options, Brantley-Sieders aims to arm breast cancer patients with the tools they need to battle this disease with a healthy dose of humor, grace, and hope.